Neoliberalism in the Amazon. Markets, conflicts and cultural struggles - Tobón, Marco (Geografares, 2024)
This article also reflects on how neoliberal policies, as government practices and narratives, aim to govern indigenous territories and their ecosystems in the Colombian Amazon. The experiences of REDD+ programs will be addressed as economic and political mechanisms that intervene in ecosystems as spaces of investment and sources of profit. The proposed approach promotes discussion around the concept of the duck-bill platypus by Brazilian sociologist Francisco de Oliveira (2003), which allows thinking about the Amazonian realities gone through economic attributes, conflicts and different relations, where neoliberal policies, for example, can feed off backwardness, and financial capital is imbued with precariousness, giving dialectical form to a reality in permanent contradiction. Finally, it will focus on how the Amazonian peoples are debating between the commercialization of the so-called “environmental services” and the mobilizations of their cultural practices as a common refuge before the machinery of capital.
Keywords: neoliberalism; REDD+; Amazonia; indigenous peoples